Enterobacter hormaechei: an endophytic bacterium found in Avocado Peel (Persea americana Mill.) with antioxidant properties - Rustini, Rustini; Rahmi, Khalila Rahmi; Putra, Purnawan Pontana; Andayani, Regina Andayani; Dwinatrana, Khiky (Pharmaciana, 2024)
Avocado peels (AVP) are renowned for their potent antioxidant properties, making them highly effective in preventing oxidation and free radical formation. Endophytes, microorganisms residing within plant tissues, have demonstrated the ability to produce novel compounds with remarkable biological activities. These bioactive compounds are sometimes even more potent than those found in their host plants. This study explores the potential of endophytes from avocado peels as rich sources of antioxidant compounds. AVP samples are collected, surface-sterilized, and segmented before being cultured in growth media. The bacteria are then isolated, purified, and subjected to ethyl acetate extraction to evaluate their antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) microassay. Samples demonstrating favorable antioxidant properties undergo molecular identification through 16S rRNA gene sequencing. Four bacterial strains are successfully isolated, with only the APK4 strain exhibiting significant antioxidant activity with an IC50 value of 302.3 μg/mL. Molecular analysis and phylogenetic tree construction reveal that APK4 is closely related to the Enterobacter hormaechei species, with a percent identity value of 99.93%. These findings highlight the potential of active metabolites from endophytic bacteria in AVP extracts as promising lead compounds for the development of novel drugs, nutraceuticals, and cosmetic ingredients.